Effects of heavy metals in bauxite from school environment on respiratory health and biomarkers of exposure among primary school children in Pahang, Malaysia - Feisal, Nur Azalina Suzianti (2020)
Mining activities pose a serious threat to human health and the general environmental ecosystem in Malaysia and globally. This study was to determine the relationships between heavy metals in school environments with reported health symptoms, lung function, and biomarkers among primary students. A comparative cross-sectional study was carried out on 148 students in the studied group and 122 students in the comparative group. Heavy metals in the air (n=48), dust (n=32), and soil (n=28) of school environments monitored using Gillian personal sampling pump and 400W vacuum cleaner. Reported health symptoms were gathered using questionnaire. Chestgraph HI-105 was used for lung function measurement. Heavy metals were analysed using Inductively Coupled Plasma Mass Spectrometry. Data analysis was carried using SPSS analysis. The concentration of PM10 and heavy metals in environment was significantly higher in the studied area. The highest heavy metal concentration in all school environments was Ni in the studied area. Highest reported symptoms among students in the studied area were cough with flu (48.0%) followed by nasal congestion (45.9%), runny nose (42.6%) and headache (41.2%). While in comparative group was cough with flu (35.9%) and cough only (35.2%) for the past 3 months. Symptoms such as headache, dizziness, diagnosed asthma, runny nose, nasal congestion, sore throat, dry throat, chest tightness after outdoor activities and itchiness showed significant differences between two groups. This study also showed students in studied area have significantly lower lung functions ratio with 68.2% FEV1 abnormalities followed by 50% of FEV1/FVC and 38.5% of FVC. All heavy metals accumulated in hair and toenails were significantly higher in studied group than the comparative group. Pb accounted for the highest heavy metal accumulation detected in hair with 18.14 μg/g while Ni accounted for the highest heavy metal accumulation detected in toenails with 6.13 μg/g. Higher pollutants concentration of PM10 and heavy metals concentrations in indoor air, window dust and corridor dust were significantly associated with all reported health symptoms except for cough and chest tightness at night. PM10 and heavy metals exposure in school environments especially air, window dust and corridor dust were significantly associated with reduction of lung functions. Findings showed there was significant relationship between heavy metals in environment with heavy metals accumulation in biomarkers. This study indicated the association of heavy metals concentration in biomarkers with all reported health symptoms. Lower values of lung functions were found significantly associated with runny nose, nasal congestion, dry throat, chest tightness, chest tightness at night and chest tightness after outdoor activities. Logistic regression showed increasing exposure to heavy metals in indoor air and dust to health symptoms and lung function. Increasing exposure to heavy metals in environment increase the concentrations of heavy metals in biomarkers. This study found that school location to mining area and Ni concentrations in indoor air and dust were the two risk factors for health outcomes among students. Since it is near the school location, proper zoning implemented for school location, mining companies should have appropriate standard operating procedures (SOP) and cleanliness should be emphasized.